Effectiveness of red yeast rice on carotid atherosclerosis: A systematic review and meta-analysis - Wang, Shuai; Chen, Yue; Wang, Rui; Ma, Bailing; Wang, Zhenzhen; Tang, Guanguang; Wang, Siyu; He, Yi; Qu, Liping (Frontiers in Pharmacology, 2022)
Literatures on red yeast rice (RYR), a traditional Chinese medicine, showed the preventive and therapeutic effects on carotid atherosclerosis by decreasing low-density lipoprotein cholesterol (LDL-C) and other risk factors. However, evidence remain inconsistent. The study aimed to further detect the effects of RYR for carotid atherosclerosis. Several databases were searched for original trials of RYR in treatment of carotid atherosclerosis, reporting plaque indicators. Carotid plaque area (AREA), carotid plaque score (SCORE), and intima-media thickness (IMT) were set as primary outcomes. Lipid profile and safety indicators were set as secondary outcomes. Meta-analyses were performed in randomized controlled trials (RCTs) by Comprehensive Meta-analysis software. Heterogeneity was evaluated by using the I2 index and Q statistic. Subgroup, sensitivity, and dose-effect analyses were conducted. Twenty studies of RCTs with 2217 patients were included. Compared with control group, AREA (SMD = −0.855, 95%CI: −1.259~−0.451, P < 0.001), IMT (SMD = −0.588, 95%CI: −0.792~−0.384, P < 0.001), SCORE (SMD = −0.708, 95%CI: −1.135~−0.282, P = 0.001), LDL-C (SMD = −0.938, 95%CI: −1.375~−0.502, P < 0.001), triglyceride (SMD = −0.766, 95%CI: −0.980~−0.551, P < 0.001), and total cholesterol (SMD = −0.858, 95%CI: −1.254~−0.462, P < 0.001) were significantly decreased and HDL-C (SMD = 0.389, 95%CI: 0.044~0.733, P = 0.027) was significantly increased in RYR therapy. Indicators of safety were no significant and stable difference between the two groups (P > 0.050). Heterogeneities mainly come from the treatment time or control group setting. Most results were no change in sensitivity analysis. Dose-effect relationship existed in these indicators except TC and HDL-C. We concluded that RYR therapy showed considerable efficacy and safety profile for carotid atherosclerosis in Chinese population.